New tools and communication technologies for people handicapped physically, intellectually and socially as well as senior citizens - Sahaj, Tomasz (Virtualizing the lives of people with disabilities, 2021)
The aim of the article is to present and describe chosen tools and technology, applications and Internet environments which enable a remote and indirect communication, the supervision and care of senior citizens and people with physical, intellectual and social disabilities. Some of these solutions – such as telecare – grew in considerable importance in the age of the COVID-19 pandemic, which in 2020 caused social isolation twice together with lockdown, forcing communication, education and work to be remote. Solutions discussed in the text are of different provenance: animated by single social actors, commercial institutions or social organizations, but also comprehensive solutions of government applications. What links all of the solutions is the fact that supporting people socially marginalised and handicapped, in particular with hearing, sight and speech disorders, they facilitate communication and social integration.